Implementing ‘Good Informed Consent Practices’ in Malaysian healthcare facilities: Balancing the demands of law and medical realities - Hazelan, Hairul Akram; Jahn Kassim, Puteri Nemie (2018)
The Doctrine of Informed Consent requires medical practitioners to provide adequate information to their patients so that they are able to understand the nature and consequences of the proposed treatment. Failure to provide such information to their patients may trigger claims in the court of law. This point has been reiterated by the recent Federal Court judgement in Zulhasnimar Hassan Basri & Anor v. Dr Kuppu Velumani P & Ors [2017] which re-emphasized the judgement of the Federal Court in Foo Fio Na v Dr Soo Fook Mun & Anor [2007] that “the practitioner is duty bound by law to inform his patient who is capable of understanding and appreciating such information of the risks involved in any proposed treatment so as to enable the patient to make an election of whether to proceed with the proposed treatment with knowledge of the risks involved or decline to be subjected to such treatment.” In this respect, informed consent is not just an established ideal legal theory but a collaborative process involving (i) disclosure of pertinent information by the medical practitioner (ii) comprehension by the patient (iii) voluntary agreement. Nevertheless, factors such as complexity of communication in clinical encounters involving language barriers, age and intellectual ability of the patient may undermine effective informed consent processes. Thus, it is imperative that healthcare facilities establish ‘good informed consent practices’ that considers the current realities surrounding patients’ circumstances as well as adhering to the demands made by the court of law. This will eventually reflect the autonomous wishes of the patients as required by law as well as safeguarding medical practitioners and health facilities against potential and increasing law suits.